Fairness and inequality acceptance in children and adolescents: A survey on behaviors in economic experiments - Daniel Schunk; Isabell Zipperle (Journal of Economic Surveys, 2023)
This survey article provides an overview of the recent experimental economic literature on fairness-related behaviors in children and adolescents. We discuss different motives underlying fair behavior, summarize the development of fairness and inequality acceptance across different developmental stages, and we shed light on behavioral heterogeneity with respect to gender, SES, and cultural background. Moreover, we also discuss the role of preferences and social norms as determinants of fair behavior in children and adolescents. To learn about the origins of fair behavior, we address the influence of social environments, such as the family and we discuss the potential contribution of the genetic disposition.
Keywords: 330; children and adolescents; experiment; fairness; inequality acceptance; social norms; social preferences